1997
DOI: 10.1159/000259242
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Cochlear and Retinal Degeneration in the tubby (rd5) Mouse

Abstract: Mice homozygous for a defect of the tub (rd5) gene exhibit cochlear and retinal degeneration combined with obesity, and resemble certain human autosomal recessive sensory deficit syndromes. To establish the progressive nature of sensory cell loss associated with the tub gene, and to differentiate tub-related losses from those associated with the C57 background on which tub arose, we evaluated cochleas and retinas from tub/ tub, tub/+, and +/+ mice, aged 2 weeks to 1 year by light and electron microscopy. Cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Programmed cell death has been proposed as the cause of both retinal and cochlear degeneration in tubby mice (16,17), and this has now been formally demonstrated for retinal degeneration by our data as well as a very recent report (9). This result suggests that Tub function is important for the survival of retinal photoreceptor cells in the adult animal.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Programmed cell death has been proposed as the cause of both retinal and cochlear degeneration in tubby mice (16,17), and this has now been formally demonstrated for retinal degeneration by our data as well as a very recent report (9). This result suggests that Tub function is important for the survival of retinal photoreceptor cells in the adult animal.…”
Section: Discussionsupporting
confidence: 85%
“…Earlier studies have shown that tubby mice exhibit early progressive retinal degeneration, possibly due to apoptosis (16,17). Photoreceptor cells, the main cell type lost, have been shown to express Tub (19).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…4c). Although both hair and spiral ganglion cell degeneration first occur in tubby mice 15,16 by 20 weeks, functional defects assessed by ABR analysis are apparent at only 3 weeks 11,15 , suggesting that the degeneration of these cells might be a secondary event. As hearing loss in tubby mice was rescued by the 129P2/OlaHsd allele of Mtap1a, which is expressed specifically in the spiral ganglion cells, the tubby gene may significantly influence auditory signal transmission in these cells.…”
mentioning
confidence: 99%
“…Tubby, an autosomal recessive syndrome in mice, is characterized by maturity-onset obesity, insulin resistance, infertility, and progressive cochlear and retinal degeneration (1)(2)(3). The tubby phenotype resembles human sensory/obesity syndromes such as Alstrom's and Bardet/Biedl that are characterized by combined cochlear hair cell and retinal photoreceptor loss accompanied by infertility and moderate late-onset obesity (4 -6).…”
mentioning
confidence: 99%